2020
DOI: 10.1177/1758835920963001
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 protein expression and copy number gains in HIV-positive locally advanced cervical cancer

Abstract: Background: The programmed death-1/programmed death-ligand-1 (PD-1/PD-L1) axis may represent a target for cervical cancer; however, it is poorly understood in human immunodeficiency virus (HIV)-infected patients. Methods: We evaluated HIV-positive ( n = 42) and HIV-negative ( n = 110) women with locally advanced cervical cancer regarding their PD-L1 expression, determined by combined positive score (CPS) ⩾ 1 and tumor proportion score (TPS) ⩾ 25%, and PD-L1 copy number alterations, assessed by fluorescence in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…39,40 A previous study of HIV-positive patients with cervical squamous cell carcinoma showed that PD-L1 þ tumor cells are more radiosensitive and that those patients show better response with RT. 35 High CD8:FOXP3 ratio combined with negative PD-L1 expression was an independent and significant favorable predictive factor for local control. It is reported that it might be a useful biomarker of radiosensitivity in patients with laryngeal SCC receiving definitive RT.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 88%
See 2 more Smart Citations
“…39,40 A previous study of HIV-positive patients with cervical squamous cell carcinoma showed that PD-L1 þ tumor cells are more radiosensitive and that those patients show better response with RT. 35 High CD8:FOXP3 ratio combined with negative PD-L1 expression was an independent and significant favorable predictive factor for local control. It is reported that it might be a useful biomarker of radiosensitivity in patients with laryngeal SCC receiving definitive RT.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 88%
“…CD4 count correlated positively with PD-L1 CPS higher than 1% and negatively with TPS higher than 25% in HIV-positive patients with cervical squamous cell carcinoma. 35 Such discrepancies may be attributed to a relatively small number of cases tested and different methodology in evaluating PD-L1 and different tumor microenvironments of cervical and anal SCC. Besides, it has been postulated that a decrease in CD4 count may result in decreased PD-L1 expression on tumor cells and antigen-presenting cells, secondary to decreased interleukins (IL-2) and interferon-c in the microenvironment.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copy number ampli cation or deletion often results in abnormal expression of oncogene and tumor suppressor genes, as well as tumor cells abnormalities, including cell adhesion and recognition [43]. Prior evidence has con rmed that an increase in the copy number of the PD-L1 gene was closely associated with the anti-PD-1 / PD-L1 treatment of locally advanced cervical cancer [44]. Therefore, we analyzed the copy number pro le of 138 samples from TCGA cohort and grouped samples according to risk score after the removal of germline CNV data.…”
Section: Discussionmentioning
confidence: 99%
“…CPS is obtained by the total number of PD‐L1 positive cells, including tumor cells, lymphocytes, and macrophages, divided by the total number of living tumor cells ×100. 22 When CPS≥1, PD‐L1 expression was positive.…”
Section: Methodsmentioning
confidence: 98%